Ranking, coordination, and global governance: The case of the Access to Medicine Index. (21st December 2018) - Quak, Sander; Heilbron, Johan; Meijer, Jessica
Abstract: As a case study in the proliferation of global rankings, we examine the initiation, construction of, and response to the Access to Medicine Index, which ranks pharmaceutical companies according to their respective contribution to access to medicine for developing countries. Since it has served as the model for constructing global rankings in the fields of nutrition, seeds, mining, possibly in the future, oil, seafood, mobile internet, and agricultural commodities, and it serves as a blueprint for the development of corporate sustainability benchmarks in line with the United Nations Sustainable Development Goals, its significance goes well beyond public health. From an economic-sociological perspective we argue, first, that rankings can be conceived as symbolic classifications that serve predominantly as market-based coordination devices. To understand the proliferation of global rankings, we argue, secondly, that they are an integral part of the changing balance of power in the domain of global public health consisting of a historical shift from international organizations as the central mode of governance and coordination to a more decentralized and diversified global field structure. This global field is formed by an increasing number and variety of actors, but lacks a central decision-making body. The case of the Access to Medicine Index suggests that a historical-sociological field perspective has analytical advantages over both the micro-analysis of socio-technical devices and macro-level approaches to issues of governance in contemporary capitalism.